Tin(ii) cations stabilized by non-symmetric N,N′,O-chelating ligands: synthesis and stability - Novák, Miroslav; Turek, Jan; Milasheuskaya, Yaraslava; Syková, Miriam; Dostál, Libor; Stalmans, Jesse; Růžičková, Zdeňka; Jurkschat, Klaus; Jambor, Roman (Royal Society of Chemistry, 2023)
A series of novel non-symmetric neutral N,N',O-chelating ligands derived from the alpha-iminopyridine 2(C(R-1)=N(C6H3-2,6-iPr(2)))-6-((RRP)-R-2-P-3=O)C5H3N (L-1: R-1 = H, R-2 = R-3 = Ph; L-2: R-1 = Me, R-2 = R-3 = Ph; L-3: R-1 = H; R-2 = Ph, R-3 = EtO; L-4: R-1 = Me, R-2 = Ph, R-3 = EtO; L-5: R-1 = H, R-2 = R-3 = iPrO; L-6: R1 = Me, R-2 = R-3 = iPrO) were synthesized. Ligands L(1-6 )were reacted with SnCl2 and Sn(OTf)(2) with the aim of studying the influence of different (RRP)-R-2-P-3=O functional groups on the Lewis base mediated ionization of SnCl(2 )and Sn(OTf)(2). While all ligands L1-6 provided the corresponding ionic tin(II) complexes [L1-6 ->+ SnCl](+)[SnCl3](-) (1-6), only ligands L-1, L(4 )and L-6 were able to stabilize tin(II) dications [L-1,L-4,L-6-+ Sn(H2O)][OTf](2 )(7-9). The auto-ionized compounds [L3-6-+ SnCl](+)[SnCl3](-) possessing ethylphenyl phosphinate and diisopropylphosphite substituents undergo elimination of EtCl and iPrCl, respectively, yielding compounds 10-13. These can either be interpreted as neutral tin(II)phosphinate chloride (10, 11) and tin(II)phosphonate chloride (12, 13), respectively, containing Sn-O and Sn-Cl bonds, and a P=O -> SnCl2 interaction, or as zwitterionic compounds, where the positive charge of the central tin atom is compensated by an [OSnCl2]- anion. Finally, DFT studies were performed to better understand the steric and electronic properties of the ligands L(1-6 )as well as the nature of the bonds in the resulting products, with a particular focus on complexes 10-13.
Cínaté kationty stabilizované nesymetrickými N,N',O-chelatujícími ligandy: syntéza a stabilita
Keywords: Tin; chelating ligands; NMR; cín; chelatující ligand; NMR; hemilabilita